Techno-economic analysis of offshore isothermal compressed air energy storage in saline aquifers co-located with wind power. (1st December 2021) - Bennett, Jeffrey A.; Simpson, Juliet G.; Qin, Chao; Fittro, Roger; Koenig, Gary M.; Clarens, Andres F.; Loth, Eric
Graphical abstract: Highlights: Intermittency remains a challenge for offshore wind energy. Offshore saline aquifers are well suited for compressed air energy storage. Round-trip efficiency higher than traditional CAES using near-isothermal machinery. Cost less than batteries for storage over 10 h. Wind farm revenue increases by 55%, at a lower LCOE than batteries. Abstract: Offshore wind power projects are increasingly attractive in many regions even though capacity is impacted by intermittency as it is with other renewable power sources. We examine balancing the intermittency with an Offshore Compressed Air Energy Storage (OCAES) system that combines near-isothermal compression and expansion processes via water spray injection with air storage in saline aquifers. Spray injection maintains the air at nearly constant temperatures to improve round-trip efficiency, and saline aquifers are abundant in near-shore environments at suitable depths. This techno-economic analysis estimates the efficiency, cost, and value of OCAES, and demonstrates it in the context of the Atlantic coast of the United States, for a wind lease near Virginia. The round-trip efficiency of the OCAES system is projected using a thermal fluid process model that accounts for machinery performance as well as geophysical subsurface characteristics and gradients. Cost estimates are based on combining axial gas turbine technology with water spray injection retrofits and drilling experience from the oil and gas industry. Value to the electric grid is quantified with a price-taker dispatch model that optimizes the value of delivered electricity. The study analyzed power capacities from 10 to 390 MW, and our results show that for the geophysical conditions considered, a 200 MW OCAES system is expected to have a round-trip efficiency of 77% and a capital cost of $1457/kW. When paired with a 500 MW wind farm, OCAES is able to increase revenue from $0.031/kWh, without storage, to $0.048/kWh. We also show that a 350 MW OCAES system with 168 hours of storage is able to make the wind farm power output constant with a levelized cost of electricity (LCOE) of $0.22/kWh, 81% less than with 10-hour lithium-ion battery technology.